2009
DOI: 10.1080/03043790903047503
|View full text |Cite
|
Sign up to set email alerts
|

A multicultural, multidisciplinary short course to introduce recently graduated engineers to the global nature of professional practice

Abstract: Since 2001, the International Institute of Women in Engineering (IIWE) at EPF, Ecole d'ingenieurs generaliste, Sceaux, France, has conducted a 3 week short course for culturally and discipline diverse, recently graduated and final year engineering students. The aim of this course is to introduce young engineers to broad global concepts and issues relating to their future professional practice, through intercultural learning. The initial course programme provided examples of engineering practices in various cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…These papers address the topic of culture, with the discussion focusing on educational projects in which participants were tasked to collaborate with people from other countries either directly (Arzberger et al, 2010;Jesiek, Haller, & Thompson, 2014;Mehalik, Lovell, & Shuman, 2008;Meunier, Dutto, Guillet, & Michau, 2007) or in geographically distributed virtual teams (Davies, Zaugg, & Tateishi, 2014;Gonzalez, Guerra-Zubiaga, Orta, & Contero, 2008;May, Wold, & Moore, 2015;McNair, Paretti, & Kakar, 2008;Zaugg & Davies, 2013). These authors, together with Downey et al (2006), LaFave et al (2015, Friesen and Ingram (2013), Hazelton, Malone, andGardner (2009), andSoibelman et al (2011), focus on the ability of graduates or professional engineers to work with others who have been raised or educated in "foreign" cultures (Swearengen, Barnes, Coe, Reinhardt, & Subramanian, 2002), countries, or language backgrounds.…”
Section: Close Readingsmentioning
confidence: 99%
“…These papers address the topic of culture, with the discussion focusing on educational projects in which participants were tasked to collaborate with people from other countries either directly (Arzberger et al, 2010;Jesiek, Haller, & Thompson, 2014;Mehalik, Lovell, & Shuman, 2008;Meunier, Dutto, Guillet, & Michau, 2007) or in geographically distributed virtual teams (Davies, Zaugg, & Tateishi, 2014;Gonzalez, Guerra-Zubiaga, Orta, & Contero, 2008;May, Wold, & Moore, 2015;McNair, Paretti, & Kakar, 2008;Zaugg & Davies, 2013). These authors, together with Downey et al (2006), LaFave et al (2015, Friesen and Ingram (2013), Hazelton, Malone, andGardner (2009), andSoibelman et al (2011), focus on the ability of graduates or professional engineers to work with others who have been raised or educated in "foreign" cultures (Swearengen, Barnes, Coe, Reinhardt, & Subramanian, 2002), countries, or language backgrounds.…”
Section: Close Readingsmentioning
confidence: 99%
“…Haciendo una revisión a nivel internacional de la educación en ingeniería industrial, se observa como tendencia en varios autores: (Lappalainen, 2010), (Larsen, 2009), (Fernandez, 2009), (Hazelton, 2009), (Sharma, 2009), la de integrar el conocimiento científico y tecnológico con el humanístico. ¿Podría esto obedecer al cambio de concepción que ha tenido el modelo desarrollista, que habiendo caído en crisis al privilegiar la educación científica y tecnológica por encima de la humanista, ahora trata de vincular conceptos como multiculturalidad, interdisciplinariedad y ecología tanto al entorno organizacional como al educativo atribuyéndole a esta vinculación el éxito y la pertinencia que los nuevos modelos educativos requieren?.…”
Section: Consideraciones Finalesunclassified
“…A similar situation pertains throughout the rest of the world (Azapagic et al, 2005;Desha et al, 2009;Hazelton et al, 2009), and it has been suggested (Porritt, 2007) that; (2004): university policy, number of sustainable development related courses and specializations at both undergraduate and postgraduate levels, the degree to which universities promote the embedding of sustainable development in curricula and the extent of adoption of an environmental management system in-house by universities. The EESD survey is self reporting however, and this leads to a situation whereby all institutions for example are (self) credited with either completely embedding sustainability into their engineering programmes (100% rating) or not at all (0% rating).…”
Section: Sustainability In Engineering Education; the Current Situationmentioning
confidence: 99%